Mengajarkan Bahasa Arab Kepada Anak-Anak Usia Dini Dengan Buku Modul Al-Lughotul ‘Arabiyah Direktorat KSKK Madrasah RI - Dhaifina Amalia; Darsita Suparno; Umi Kulsum; Mauidlotun Nisa; M.Zacky Mubarok (MUMTAZA Journal of Arabic Teaching, Arabic Linguistic and Literature, 2025)
This study employs a qualitative approach with a literature study design to explore the use of the Al-Lughotul 'Arabiyah printed module in teaching Arabic to early childhood learners in Islamic elementary schools (madrasah ibtidaiyah). The main subject of the analysis is the Grade 2 Arabic language module published by the Directorate of KSKK Madrasah, Ministry of Religious Affairs of the Republic of Indonesia in 2020. The data were analyzed by identifying the module's content structure, instructional approach, types of learning activities, and the relevance of the themes to the developmental needs of young learners. The analysis focused on how the module facilitates communicative, visual, and thematic learning tailored to the cognitive characteristics of early learners. Data analysis techniques included in-depth reading, thematic categorization, and interpretation of the instructional meaning embedded in the module. Validity was ensured by comparing the module content with theories of early childhood language learning and the curriculum document KMA No. 183 of 2019. The findings show that the module emphasizes contextual, activity-based learning, vocabulary repetition, phonetic practice, and the integration of social and religious values. This study provides insight into how government-issued Arabic textbooks can serve as effective media for developing Arabic language learning from an early age.